Loss of the tight junction proteins occludin and zonula occludens-1 from cerebral vascular endothelium during neutrophil-induced blood-brain barrier breakdown in vivo. - Bolton, S; Anthony, D; Perry, V (1998)
The tight junctions found between cerebral vascular endothelial cells form the basis of the blood-brain barrier. Breakdown of the blood-brain barrier is a feature of a variety of CNS pathologies that are characterized by extensive leucocyte recruitment, such as multiple sclerosis and stroke. The molecular mechanisms associated with opening of the blood-brain barrier and leucocyte recruitment in vivo are currently poorly understood. We have used an in vivo rat model to investigate the molecular response of the CNS endothelium to neutrophil adhesion and migration. Injection of interleukin-1 beta into the striatum of juvenile brains results in a neutrophil-dependent increase in vessel permeability at 4 h. Only a subset of blood vessels were associated with neutrophil recruitment. These particular vessels displayed an increase in phosphotyrosine staining, loss of the tight junctional proteins, occludin and zonula occludens-1, and apparent redistribution of the adherens junction protein vinculin. Examination of these vessels under the electron microscope indicated that the cell-cell adhesions in such vessels are morphologically different from normal junctions. This study provides the first direct evidence in vivo that leucocyte recruitment can trigger signal transduction cascades leading to junctional disorganization and blood-brain barrier breakdown. Our results have established an endothelial cell molecular profile associated with leucocyte-induced blood-brain barrier breakdown in vivo, and the relevance of different in vitro cell culture models may now be viewed more objectively.